One shot alpha numeric weight based clustering algorithm with user threshold - Prasad Maradana, Durga Venkata; Thota, Srikanth (Journal of Autonomous Intelligence, 2024)
Information Retrieval from Files and data bases like data sources is a major issue now days. After Information Retrieval clustering is also a one of the important things. In the market so many clustering algorithms were available. But choosing of the clustering algorithm depends on the user requirements. This paper addresses the study of agglomerative approach for different constraints or metrics or user preferences like Number of levels in the clustering process, number of clusters that should be generated at each level and range of the attributes at each level for doing the clustering for the given data set. In brief overview we discuss the agglomerative approach for clustering algorithm with their user preferences.